The Moderating Effect of Firm Size on Determinant Factor of Firm Value of IDX F&B's Subsector - Junaidi, Rahmat; Lumbanraja, Maha Martabar Mangatas; Berampu, Lailan Tawila; Firmansyah, Sukri (Journal of Applied Business Administration, 2024)
Research early finding show us that Food & beverages's (F&B) industry facing the competion to maintain the sustainability amidst tight competition in various economy sector. This requires companies in F&B trying to be seen as companies that are worthy of investment for potensial investors, one of which is by increasing the value of the company. This research aims to examine the influence of Earning Per Share (EPS) & Debt to Equity Ratio (DER) on Firm Value with Firm Size as a Moderating Variable (Study of Food & Beverages Subsector Companies Listed in BEI 2017-2021). The observation emiten in this study were companies listed on F&B subsector of the Indonesia Stock Exchange from 2017 to 2021, with a total of 32 of total 72 companies by purphosive sampling method that contains of 160 Financial Statement. This research uses Structural Equation Modeling-Partial Least Square (SEM-PLS) to analyze the data, show that EPS and DER has a positive and significant effect on Firm value, but Firm size is unable to moderate either relationship between EPS and DER to Firm Value.